Royal figure depicted in the Tribhanga pose - Temples of India Project Team (Jio Institute, 2024)
A heavily adorned royal figure, depicted in the tribhanga pose, exhibits damaged hands. Whether this represents the patron, King Vigraharaja IV, remains a matter of pure speculation.